Mandrill mothers associate with infants who look like their own offspring using phenotype matching - Charpentier, Marie JE; Poirotte, Clémence; Roura-Torres, Berta; Amblard-Rambert, Paul; Willaume, Eric; Kappeler, Peter M; Rousset, François; Renoult, Julien P (eLife, 2022)
Behavioral discrimination of kin is a key process structuring social relationships in animals. In this study, we provide evidence for discrimination towards non-kin by third-parties through a mechanism of phenotype matching. In mandrills, we recently demonstrated increased facial resemblance among paternally related juvenile and adult females indicating adaptive opportunities for paternal kin recognition. Here, we hypothesize that mandrill mothers use offspring’s facial resemblance with other infants to guide offspring’s social opportunities towards similar-looking ones. Using deep learning for face recognition in 80 wild mandrill infants, we first show that infants sired by the same father resemble each other the most, independently of their age, sex or maternal origin, extending previous results to the youngest age class. Using long-term behavioral observations on association patterns, and controlling for matrilineal origin, maternal relatedness and infant age and sex, we then show, as predicted, that mothers are spatially closer to infants that resemble their own offspring more, and that this maternal behavior leads to similar-looking infants being spatially associated. We then discuss the different scenarios explaining this result, arguing that an adaptive maternal behavior is a likely explanation. In support of this mechanism and using theoretical modeling, we finally describe a plausible evolutionary process whereby mothers gain fitness benefits by promoting nepotism among paternally related infants. This mechanism, that we call ‘second-order kin selection’, may extend beyond mother-infant interactions and has the potential to explain cooperative behaviors among non-kin in other social species, including humans.
Keywords: primate; African monkey; mandrillus sphinx